Allosteric Targeting of Aurora A Kinase Using Small Molecules: A Step Forward Towards Next Generation Medicines? - Panicker, Resmi C.; Coyne, Anthony G.; Srinivasan, Rajavel (Current Medicinal Chemistry, 2019)
Background: Aurora A (AurA) kinase is a key mitotic protein implicated in cancer. Several small molecule inhibitors targeting the ATP binding site of this enzyme are in various stages of clinical development. However, these inhibitors can result in selectivity and drug resistance problems. Allosteric inhibition of kinases using small molecules is an alternative strategy to target these enzymes selectively and these could serve as the seeds for next generation medicines. This review discusses the developments in the non-ATP site binding small molecule inhibitors of AurA and their prospect as future therapeutics. Discussion: Allosteric targeting of AurA kinase using small molecules is relatively a new strategy, and only a handful of research work has been reported. Two patents and three papers pertaining to allosteric targeting of AurA kinase using small molecules were covered in this review. Topics discussed include, identification of small molecule inhibitors targeting AurA- Targeting Protein for Xenopus kinesin-like protein 2 (TPX2) interaction, anacardic acid - a natural product ligand that selectively modulates AurA activity in the presence of Aurora B kinase, and identification of felodipine as an uncompetitive inhibitor of AurA using Surface Enhanced Raman Spectroscopy (SERS) technique. Conclusion: Allosteric targeting of therapeutically relevant enzymes using small molecules is a burgeoning research area. New techniques such as fragment-based ligand discovery, SERS methods, etc., are expanding to identify the allosteric site binding ligands. Research in this area is expected to deliver fruitful outcome in terms of novel therapeutics against AurA kinase as well as other therapeutically relevant enzymes.
Keywords: AurA-TPX2 inhibition